L'architecture du xxe. siecle - Champigneulle, Bernard; Ache, Jean (Paris : Presses universitaire, 1962)
Arquitectura y tecnología años 1895-1960
Keywords: ARQUITECTURA MODERNA; ARQUITECTURA; HISTORIA; TECNOLOGIA; SIGLO XIX; SIGLO XX